Attack context: an important mediator of the relationship between psychological status and asthma outcomes. Issue 3 (1st March 2002) - Greaves, C J; Eiser, C; Seamark, D; Halpin, D M G
Abstract : Background: The importance of psychosocial variables in asthma is increasingly recognised, although attempts to relate these to asthma outcomes often produce only weak relationships. This study aimed to identify whether such relationships might be obscured by the effects of recent asthma experience on psychological status. Methods: An adult community sample of 37 patients who had suffered a recent attack of asthma and 37 with stable asthma were given measures of panic fear and control confidence. The relationship with subsequent emergency service use was examined using two way ANOVA and correlational analyses. Covariate influences (psychiatric morbidity, age, sex, treatment level, asthma duration, social status) were considered. Results: Control confidence predicted emergency service use in different ways for recent attack and stable asthma patients. This interaction was highly significant (F(1, 69) = 10.32, p<0.005) with high confidence relating to an increased risk of an attack in the recent attack group and low confidence relating to increased risk for the stable asthma group. There was also an interaction between panic fear and attack context (F(1, 69) = 11.05, p<0.005) with low panic fear resulting in more attacks for recent attack cases. Conclusions: Attack context (having a recent attack) is an important mediator of psychological status. Strong cognitive/affective responses to attacks may motivate improved self-care and this represents a window of opportunity for self-care interventions. Weak cognitive/affective responses to attacks may reflect denial and require different intervention approaches. For those with recently stable asthma the relationships are qualitatively and quantitatively different, and the implications for intervention are also discussed.